EFEKTIVITAS PENDEKATAN SCIENCE ENVIRONMENT TECHNOLOGY AND SOCIETY BERBASIS CTL TERHADAP HASIL BELAJAR - Arif Rahman Hakim; Muhammad Sururuddin; Nur Haqiqi (Program Studi PGSD Universitas Flores, 2021)
This study aims to determine the effectivenes of the CTL based SETS approach to student science learning outcomes in fourth grade. This type of research used in this study is an experimental research design using one group pretest-posttes. The sample used was 27 peoples who were grade IV. Data collection techniques using observation and test descriptions to determine student learning outcomes that are assessed using an assessment rubric. Before the data were analyzed, the instrument was tested for validity and reliability. After the research was carried out and the data collected, the pre-test and post-test results were analyzed. The pretest result reached an average of 64.98 into the sufficient category. Then at the posttest the average overall score is 71.28 in the good category. For the requirement test, data analysis was carried out by using the chi-square normality test, while the hypothesis testing technique used the t-test. Hypothesis test results obtained tcount>ttable. It means the conclution that there are differences in student science learning outcomes before and after the Science, Environment, Technology, And Society approaches are used based on CTL in grade IV SDN 6 Masbagik Selatan in the 2020/2021 academic year.